Pain modulation in the spinal cord - Woolf, Clifford J. (Frontiers in Pain Research, 2022)
The sensory inflow from the periphery that triggers innocuous and painful sensations is highly complex, capturing key elements of the nature of any stimulus, its location, intensity, and duration, and converting this to dynamic action potential firing across a wide population of afferents. While sensory afferents are highly specialized to detect these features, their input to the spinal cord also triggers active processing and modulation there which determines its output to the brain, to drive the sensory percept experienced and behavioral responses. Focus on such active spinal modulation was arguably first introduced by Melzack and Wall in their Spinal Cord Gate Control theory. This theory has had a profound influence on our understanding of pain, and especially its processing, as well as leading directly to the development of clinical interventions, and its historical importance certainly needs to be fully recognized. However, the enormous progress we are now making in the understanding of the function of the somatosensory system, means that it is time to incorporate these newly discovered features into a more complex and accurate model of spinal sensory modulation.